140 Does The Gore Septal Occluder Offer Excellent Closure of all PFO Phenotypes when Guided by 3D Imaging?. (31st May 2014) - Rekhraj, S; Vassiliou, V; Orzalkiewicz, M; Hoole, SP; Watkinson, O; Kydd, A; Boyd, J; Parker, K; McNab, D; Densem, C; Shapiro, LM; Rana, BS
Abstract : Purpose: Device characteristics are key in ensuring effective sealing of Patent Foramen Ovale (PFO). With a unique design and biocompatible material allowing device conformity to varying PFO anatomies, the Gore Septal Occluder (GSO) might be ideal for percutaneous closure of complex PFO. Methods: Between August 2011 to September 2013, 58 consecutive patients underwent PFO closure using GSO device at our institution. Indications for closure included stroke or transient ischaemic attack (n = 44), paradoxical embolus (n = 8), migraine (n = 1), decompression illness (n = 3) and shunt with hypoxia (n = 2). All patients underwent detailed assessment of PFO anatomy using 3D transoesophageal echocardiography (TEE). 'Complex' anatomical characteristics were recorded according to pre-defined criteria, see Table 1 . Results: All 58 patients (mean age 41 years; age range 17–71, male 54%) underwent successful GSO device implantation. 34/58 (59%) had one or more 'complex' PFO anatomical features as shown in Table 1 . Devices used were: 15 mm (n = 1), 20 mm (n = 8), 25 mm (n = 41), 30 mm (n = 8). Procedure and fluoroscopy times were 59 ± 11 mins and 6.3 ± 3.8 mins respectively. There were no significant post-procedure complications except one patient developed migraine and another had asymptomatic paroxysmal atrial fibrillation. An immediate assessment post procedure with TEE confirmed good positioning of the device with no evidence of shunts in 58 patients. One patient had moderate shunting, however device position was excellent. Transthoracic echocardiography (TTE) at follow-up 12 weeks post procedure has been performed in 48 patients to date. In all patients this confirmed good device position with no evidence of a shunt on colour doppler. One year follow-up bubble TTE is available on 33 patients. 21 had no residual shunting, confirming complete PFO closure. 3 patients had moderate shunting and 9 patients had mild shunting on valsalva. All patients have remained clinically well. Conclusions: 'Complex' PFO closure with the GSO device is feasible and safe. Our data suggests that the role of 3D TEE in defining 'complex' features is essential in determining device selection and the GSO device appears to be promising in these complex PFOs. Further studies are needed.